The boundaries of artisanal work and occupations in South Africa, and their relation to inequality. (3rd April 2017) - Wildschut, Angelique; Meyer, Tamlynne
ABSTRACT: Improving the access of previously marginalised groups to skilled occupations is vital to growing the South African economy and making strides to a labour market characterised by less inequality. However, under-representation of Africans and deepening gender inequality persist as challenges in artisanal employment. This quantitative picture however does little to reveal the full story of why particular inequalities in artisanal employment continue. The research employed the concept of occupational boundaries to understand how artisanal occupations were understood and how the related domain of work is described and delineated from other forms of work. The findings illustrate how the notion of artisanal work and occupations continue to be strongly constructed by race, gender, age and language in the South African context. As societies across the globe are facing either strengthening and/or new forms of inequalities, it will be critical for scholars concerned with the social and economic relations of work to (1) continue to advocate for understanding how social closure mechanisms play out in the workplace and (2) assist in broadening the gaze of research into inequality to other less understood occupational groups that play a role in perpetuating and strengthening inequalities in labour markets.